Hydrolysis rates of TMOS catalyzed by oxalic acid and stimulated by ultrasound - Vollet, D. R.; Donatti, D. A.; Ruiz, A. I. (Kluwer Academic Publ, 1999)
A simple calorimetric method was employed to study the kinetics of the hydrolysis of the solventless TMOS-water mixtures, under ultrasound stimulation, as a function of the concentration of oxalic acid. The reaction rates were obtained, in relative units, from the measured thermal peak of the reaction as a non-separated function of both the sonication time and the instantaneous temperature of the medium. For concentrations of oxalic acid below 0.01 M, polycondensation reaction starts before complete hydrolysis. For concentrations of oxalic acid above 0.01 M, hydrolysis is complete and, in addition, the inverse of the time, as measured from the starting of ultrasound action until the maximum hydrolysis heat release, was found to be a reasonable relative measure of the average hydrolysis rate constant. The average hydrolysis rate constant was found to be proportional to the square root of the molar concentration of the oxalic acid. This result is in agreement with the literature if we assume small dissociation degree for the catalyst in such a solventless alkoxyde-water medium.
Keywords: hydrolysis; TMOS; oxalic acid; ultrasound